ANALISIS KEPUTUSAN PEMUDA BEKERJA PADA USAHATANI KARET DI DESA LUBUK BATANG BARU KABUPATEN OGAN KOMERING ULU (JASEP, 2020)
The purpose of this study was to analyze the youth's decision to work in the agricultural sector, rubber centers in Lubuk Batang District, OKU Regency. This research was conducted in Lubuk Batang Baru Village, Lubuk Batang District, Ogan Komering Ulu Regency. This research was conducted in April 2017. The method used in this study was a survey method for youth in Lubuk Batang Baru Village, Lubuk Batang District, Ogan Komering Ulu Regency. The population of this study were all youths in Lubuk Batang Baru village with a population of 357. The sampling method used in this study was simple random sampling. The data collected includes primary data and secondary data. The collected data were tabulated and then processed using logistic regression analysis with the aim of analyzing youth working on rubber farming in Lubuk Batang Baru Village, Lubuk Batang District, Ogan Komering Ulu Regency. The data obtained in this study were calculated as a percentage of each component of the variable. The percentage value is used as a reference to explain quantitatively each component of the two variables. The results showed that the price of rubber (X2), the area of land owned by the family (X4) and job opportunities outside rubber farming (X5) had a significant effect on the youth's decision to work on rubber farming in Lubuk Batang Baru Village, Lubuk Batang District. Meanwhile, education (X1) and the number of siblings (X3) did not have a significant effect on youth decisions to work on rubber farming in Lubuk Batang Baru Village, Lubuk Batang District. Keywords: Youth, Decision, Farming, Rubber